Evaluasi Penerapan E-Government Melalui Aplikasi Sipaduko Pada Dinas Dukcapil Kota Jambi - Sylviana, Azna Yusra; Ariany, Ria; Koeswara, Hendri (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The results of the study show that the sipaduko application does not fully fulfill all of the five pillars of e-government maturity as a whole. the research aims to evaluate the maturity of e-government through descriptive qualitative methods with the theory by Fietkiwitz et.al (2017) through five pillars namely information dissemination (catalogue), communication, transaction, interoperability (integration) and participation. Especially on the pillars of information dissemination (catalogue), communication and participation. In the information dissemination (catalogue) pillar, it shows that the appearance of the application does not fit all age groups, then there are no information features in using the application or the latest information related to administrative services. In the communication pillar, there is not link or separate social media account for the sipaduko application, but it is incorporated in one social media service for Civil Registry Service Jambi City. On the participation pillar, the sipaduko application does not present features to involve the communication in application development. This can certainly be used as material for evaluation by Civil Registry Service in the process of developing the sipaduko application for the better, so that people’s enthusiasm for using online service is increasing.